In vitro antimicrobials activity against endemic Acinetobacter baumannii multiresistant clones - Rodríguez, Carlos Hernán (2010)
BACKGROUND: Multidrug-resistant strains of Acinetobacter baumannii have been reported increasingly around the world. The administration of an association of antibiotics has been proposed to create an active combination and to prevent the emergence of resistance. METHODOLOGY: The activity of colistin, rifampicin, gentamicin, imipenem and their associations was evaluated by means of killing curves in fourteen isolates belonging to three endemic PFGE types, in a university hospital of Buenos Aires city. The 14 isolates were selected on the basis of different mechanisms responsible for resistance to carbapenems and different susceptibility to colistin. RESULTS: The mechanism responsible for the resistance to imipenem was the production of OXA-23 and OXA-58 carbapenemases. Heteroresistance to colistin was observed in six isolates. The associations colistin-rifampicin and colistin-imipenem were synergistic in heteroresistant isolates and prevented the development of colistin-resistant mutants. The association imipenem-gentamicin was bactericidal in gentamicin susceptible isolates, whereas the association imipenem-rifampicin was always indifferent. CONCLUSION: The antimicrobial activity and the presence of synergy are related to the antimicrobials' susceptibilities irrespective of the PFGE type or the OXA-carbapenemase produced.